Hubungan Kepatuhan Diet Dan Tingkat Stres Terhadap Kadar Glukosa Darah Penderita Diabetes Mellitus Tipe 2 Di Rawat Jalan RSUD Dr Moewardi Surakarta - Wulandari, Candra Trias, Siti Zulaekah, A., M.Si, Rusjiyanto, SKM., M.Si (2014)
Introduction : Diabetes mellitus is symptom collection that appear to someone because of increasing of glucose in the blood coused by decreasing of insulin. Diet pursuance may control blood glucouse level has. Stress worsens their life style and food patient and influence blood sugar level. Goal :This reseach is aimed to know relationship between diet pursuance, level of stress and blood glucose level of type 2 diabetes mellitus patient in outpatient unit Dr. Moewardi Hospital Surakarta. Research Method : This research is classified as observation research by using Cross Sectional approach. Diet pursuance is measured by recall form for 24 days infrequently. The level of stress is measured by Holmes Rating Scale. blood glucose level data artaken from by medical record. Relationship test between patiend diet and blood glucose level and between stress level and blood glucose level of patient DM type 2 used test of Rank Spearman. Result : The result of research shows that the diet of patient that obedient 75,5% (p=0,874) with bad food amount 82,5% (p=0,959). Accuracy of food type 77,5% (p=0,596). The bad schedule 60% (p=0,780). The level stress of patient that has a heavy stress 70% (p=0,385) and bad glucose level of patient 87,5%. Conclusion : There is no relationship between relationship between diet pursuance, level of stress and blood glucose level of type 2 diabetes mellitus patient in outpatient unit Dr. Moewardi Hospital Surakarta. There is no relationship between relationship between diet pursuance, level of stress and blood glucose level of type 2 diabetes mellitus patient in outpatient unit Dr. Moewardi Hospital Surakarta.